2019
DOI: 10.1039/c8nr09564g
|View full text |Cite
|
Sign up to set email alerts
|

Insights into defective TiO2 in electrocatalytic N2 reduction: combining theoretical and experimental studies

Abstract: Defective TiO2 acts as an effective electrocatalyst for N2-to-NH3 fixation with a yield of 1.24 × 10−10 mol s−1 cm−2 and FE of 9.17% at −0.15 V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
80
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 137 publications
(82 citation statements)
references
References 57 publications
1
80
0
1
Order By: Relevance
“…In general, the Fe atom substitutes the five-coordinate Ti atom on the TiO 2 (101) surface and creation of oxygen vacancies (V) becomes more probable because of the charge compensation between the metal dopant and lattice defects. [26,53] Theunpaired electrons from V 1decorated Fe-TiO 2 present an open-shell singlet configuration (›fl), indicating the absence of Ti 3+ (Figure S16 a). This suggests that the Fe-doped TiO 2 (101) surface has more oxygen vacancies than that of pristine TiO 2 (101).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 2 more Smart Citations
“…In general, the Fe atom substitutes the five-coordinate Ti atom on the TiO 2 (101) surface and creation of oxygen vacancies (V) becomes more probable because of the charge compensation between the metal dopant and lattice defects. [26,53] Theunpaired electrons from V 1decorated Fe-TiO 2 present an open-shell singlet configuration (›fl), indicating the absence of Ti 3+ (Figure S16 a). This suggests that the Fe-doped TiO 2 (101) surface has more oxygen vacancies than that of pristine TiO 2 (101).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[1][2][3] To date,the dominant industrial route for NH 3 synthesis is the Haber-Bosch process using N 2 and H 2 as the feeding gases,b ut this process operates at high temperature and high pressure,a nd consumes al arge amount of energy while emitting CO 2 . [25] Recent studies have demonstrated that TiO 2 with oxygen defects has good electrocatalytic activity for the NRR, [26,27] and heteroatoms (B, [28] C, [29] V, [30] and Zr, [31] )a re effective dopants to enhance the NRR performances of TiO 2 catalysts. [5][6][7][8] Noble metals perform the NRR efficiently;however, their scarcity and high cost limits their application in large-scale N 2 reduction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The as-prepared TiO 2 , OV-TiO 2 -300, and OV-TiO 2 -400 nanostructures were employed as the electrocatalysts. [28,29] Furthermore, it is also an experimental evidence to verify the DFT calculation. Additionally, we also calculated the NH3 r on the basis of the area of the working electrode, which indicates that OV-TiO 2 -400 nanosheets exhibit the highest catalytic activity ( Figure S8, Supporting Information).…”
Section: Wwwadvmatinterfacesdementioning
confidence: 72%
“…TiO 2 has attracted significant research interest, principally due to its abundance, nontoxicity, and high stability . Recent studies suggest that oxygen‐defected TiO 2 is effective for the NRR . Hybridization of TiO 2 with reduced graphene oxide is an effective strategy to enhance the NRR performance .…”
mentioning
confidence: 99%